Evaluation of hay yield and quality traits of oat genotypes grown at different locations - Mut, Zeki; Erbaş Köse, Özge Doğanay; Akay, Hasan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2018)
The aim of this study was to evaluate hay yield and quality of local oatgenotypes at different locations. Twenty-five oat genotypes were evaluated in arandomized block design with four replicates at three locations during the twogrowing years. The hay yield, crude protein (CP), acid detergent fibre (ADF),neutral detergent fibre (NDF), relative feed value (RFV) and macro minerals (Ca,K, P and Mg) differed significantly with genotype (G), location (L), and year (Y).The G × L interaction was significant (P<0.05) for hay yield, crude protein andMg ratio. According to the combined results of location and years, among thegenotypes, yield varied from 8.48 to 10.78 t·ha-1, crude protein from 93.7 to 119.4 g·kg-1, acid detergent fibre (ADF) from 336.3 to 371.9 g·kg-1 and neutral detergent fibre (NDF) from 553.0 to 588.7 g·kg-1. The relative feed value (RFV) ranged from 95.5 to 106.6. G10 (10.78 t·ha-1), G8 (10.42 t·ha-1), G24 (10.40 t·ha-1), G5 (10.33 t·ha-1), G15 (10.25 t·ha-1), G12 (10.10 t·ha-1), G6 (10.08 t·ha-1), G13 (10.03 t·ha-1), G4 and G18 (9.80 t·ha-1) and G14 (9.76 t·ha-1) numbered genotypes were specified as the high yield potential genotypes. Besides, among these genotypes, G10, G5, G15, G13, G4, G18 and G14 genotypes also showed superior performance in terms of quality characteristics. Furthermore, the results obtained for K, P, Ca and Mg concentrations in this study were adequate for ruminants.